Endourological interventions in the diagnosis and management of upper urinary tract fungal infections - our experience - S Joseph Philipraj; M Joseph Thomas; Sudha Bhat (Indian Journal of Urology, 2003)
Objectives: We have analyzed the incidence and man-agement options of upper urinary tract obstructions caused by fungal infections during January 2000-December 2001. Methods: Four patients with upper urinary tract fun-gal infections underwent endourological interventions and received antifungal therapy. Results: All 4 patients underwent double J stenting, of which one patient underwent bilateral stenting. Percuta-neous nephrostomv to irrigate was done in one patient in whom the filling defect caused by the fiungal ball persisted even after 4 weeks of oral antifungal therapy. Nephroureterectomy was done in 1 patient as the renal function did not recover even after 4 weeks of appropriate therapy. Three patients had good recovery of renal func-tion. Conclusions: Endourological interventions help in re-lieving and treating obstructions caused by fungal infec-tions.